The Consul and the Hungarian Diaspora: Legal Background and Practical Considerations - Domaniczky, Endre (Review of European and Comparative Law, 2025)
The study reviews the legislation governing the relationship between the consul and the Hungarian diaspora. In doing so, we have referred to the historical background, when the consul, who basically had other tasks, was given official tasks already after the Compromise of 1867. We then saw how the Vienna Consular Convention of 1963 established a new and uniform catalogue of tasks for consuls, which, because of its acceptance, gradually became a basic standard. Hungary ratified this treaty in 1987, and initially consuls did indeed exercise their administrative and other – cultural, scientific and economic – duties as provided for in Article 5 of the VCC. Later, however, after 2010, the administrative tasks of the consuls became primary, while the other tasks, including general liaison with the diaspora, were taken over by other levels of the emerging national diaspora policy institutions. All this means that although the consul will continue to be in contact with Hungarian communities abroad and their members, and this relationship will be fundamentally shaped by the legal framework, the consul will no longer participate in this role primarily as a diplomat, but as a public administration professional.